Methods for creating academic Internet-resources for it students’ indyvidual work management - GLAZUNOVA, Olena; VOLOSHYNA, Tetyana (Journal of Education, Technology and Computer Science, 2014)
Informational and educational resources for independent work of students today are one of the most effective means. Technique of creating and using these tools requires constant research through the intensive development of of new information technologies. The present article describes the most effective tools and technologies for creating Internet resources for independent work of students of IT-specialties. Methods of their use in the educational process are The present article describes the most effective tools and technologies for creating Internet resources for independent work of students of IT-specialties, substantiated methods of their use in the educational process substantiated.